Carbon Dots in Photodynamic/Photothermal Antimicrobial Therapy - Siqi Wang; Colin P. McCoy; Peifeng Li; Yining Li; Yinghan Zhao; Gavin P. Andrews; Matthew P. Wylie; Yi Ge (Nanomaterials, 2024)
Antimicrobial resistance (AMR) presents an escalating global challenge as conventional antibiotic treatments become less effective. In response, photodynamic therapy (PDT) and photothermal therapy (PTT) have emerged as promising alternatives. While rooted in ancient practices, these methods have evolved with modern innovations, particularly through the integration of lasers, refining their efficacy. PDT harnesses photosensitizers to generate reactive oxygen species (ROS), which are detrimental to microbial cells, whereas PTT relies on heat to induce cellular damage. The key to their effectiveness lies in the utilization of photosensitizers, especially when integrated into nano- or micron-scale supports, which amplify ROS production and enhance antimicrobial activity. Over the last decade, carbon dots (CDs) have emerged as a highly promising nanomaterial, attracting increasing attention owing to their distinctive properties and versatile applications, including PDT and PTT. They can not only function as photosensitizers, but also synergistically combine with other photosensitizers to enhance overall efficacy. This review explores the recent advancements in CDs, underscoring their significance and potential in reshaping advanced antimicrobial therapeutics.